Some thoughts on Indo-European studies and ‘method’ (Atti del Sodalizio Glottologico Milanese, 2025)
Drawing on an article by Tristano Bolelli (Alcuni problemi di metodo nella linguistica indoeuropea, 1968), in which the training role of the method of Indo-European studies in linguistic studies is emphasised, this paper proposes a historiographical reconstruction of the origin of the idea that Indo-European linguistics provided a lesson in methodology starting with the work of Franz Bopp.